ANALISIS KEAMANAN JARINGAN WI-FI PUBLIK TERHADAP SERANGAN EVIL TWIN - Rakhmadi Rahman; Nurhalisah Ramli; Alya Putri Rahmadani (CV. Denasya Smart Publisher, 2026)
Public wireless networks (Wi‑Fi) are widely used in educational institutions, offices, and public areas due to their ease of access and flexibility. However, this convenience is accompanied by significant security risks, particularly Man‑In‑The‑Middle (MITM) attacks using the Evil Twin technique. This attack exploits fake access points that imitate legitimate networks to deceive users into connecting and transmitting sensitive data. This study aims to analyze the characteristics of Evil Twin attacks on public Wi‑Fi networks, evaluate the effectiveness of Deauthentication and Web Phishing techniques, and assess network monitoring tools in detecting traffic anomalies. The research method applied is an experimental approach using penetration testing in a controlled environment. Several tools such as Aircrack‑ng, Hostapd‑WPE, Wireshark, Zui, and Wi‑Fi Analyzer were utilized. The results indicate that Evil Twin attacks are highly effective in intercepting HTTP traffic and potentially compromising HTTPS sessions when users ignore digital certificate warnings. Monitoring based on metadata successfully detects abnormal traffic patterns, while the implementation of a Resilient Certificate Management System (RCMS) significantly improves network security by rejecting unauthorized certificates. This research provides practical recommendations for administrators and users to enhance public Wi‑Fi security.